1998
DOI: 10.1095/biolreprod59.3.693
|View full text |Cite
|
Sign up to set email alerts
|

Mast Cell Regulation of Human Endometrial Matrix Metalloproteinases: A Mechanism Underlying Menstruation1

Abstract: Endometrial matrix metalloproteinases (MMPs), which increase dramatically at menstruation, are purported to cause the focal tissue breakdown at menstruation, but how their expression or activation is locally regulated is unknown. Mast cell activation occurs within perimenstrual endometrium, and we postulated that mast cell products would regulate endometrial MMPs. We have examined the interaction between human mast cells and endometrial stromal cells with regard to MMP production and activation. The human mast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(32 citation statements)
references
References 48 publications
(77 reference statements)
0
30
0
1
Order By: Relevance
“…However, the physiological stimuli that induce MMP-9 production during inflammatory conditions and the role of particular cells in MMP-9 production in the lung are not fully understood. Mast cells, and in particular tryptase and TNF released from mast cells, have been implicated in the up-regulation of MMP in human aortic endarterectomy specimens (42) and in endometrial stroma cells (43), but there is no available information about the direct role of mast cells in MMP-9 release in lung or airway inflammatory conditions. Our results indicate that direct adhesive interactions between mast cells and fibroblasts, as well as mast cell mediators such as TNF, may be important for release of MMP-9 in airway inflammatory conditions.…”
Section: Discussionmentioning
confidence: 99%
“…However, the physiological stimuli that induce MMP-9 production during inflammatory conditions and the role of particular cells in MMP-9 production in the lung are not fully understood. Mast cells, and in particular tryptase and TNF released from mast cells, have been implicated in the up-regulation of MMP in human aortic endarterectomy specimens (42) and in endometrial stroma cells (43), but there is no available information about the direct role of mast cells in MMP-9 release in lung or airway inflammatory conditions. Our results indicate that direct adhesive interactions between mast cells and fibroblasts, as well as mast cell mediators such as TNF, may be important for release of MMP-9 in airway inflammatory conditions.…”
Section: Discussionmentioning
confidence: 99%
“…However, during angiogenesis, local and controlled degradation of connective tissue is essential for neovascular sprouting and elongation (Kahari & SaarialhoKere 1997). Mast cells could mediate this process since it has been demonstrated that activated MCs have the potential to stimulate the production of matrix metalloproteinases (MMPs) by endometrial stromal cells and to set up a cascade of MMP activation within the endometrium (Zhang et al 1998). It has been demonstrated that histamine and heparin have potent angiogenic effects.…”
Section: Discussionmentioning
confidence: 99%
“…Mast cell activation results in the release of potent regulators such as TNF, histamine and mast cell-specific proteases preceding menstruation (Sivridis et al 2001). The importance of such cellular interactions has been demonstrated by the production and activation of MMP1 and MMP3 by endometrial stromal cells during co-culture with mast cells (Zhang et al 1998).…”
Section: Menstruationmentioning
confidence: 99%